Development and Application of Time–temperature Indicators Used on Food during the Cold Chain Logistics. (4th December 2012) - Lu, Lixin; Zheng, Weizhou; Lv, Zhiye; Tang, Yali
Abstract : Time–temperature indicators (TTIs) are devices with a time–temperature‐dependent change to reflect food quality status and temperature history. There is increasing interest in the application of TTIs to monitor food cold chain logistics for food safety and quality. In this paper, a new enzymatic TTI based on enzyme reaction, diffusion and enzyme demobilization technology is developed. The mathematical model of TTI is drawn up, which shows the relationships between the changes of time and temperature and the diffusion length of the indicator's colour changed. To assess the reliability of TTI as the quality indicating device for perishable foods in the process of storage and transportation, fresh milk is studied as an example. Through the research of dynamic characteristics of milk and TTIs, five different TTIs that matched with the activation energy of the prototype milk were designed and tested in several constant temperature profiles and a variable temperature profile. By comparing the end response value of the prototype TTI with the effect of forecasting the shelf life of milk, it was considered that the enzyme reaction–diffusion TTI has good stability and reliability at dynamic storage conditions and could be used to monitor the shelf life of perishable food during the cold chain transportation. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Time–temperature indicators (TTIs) are devices with a time–temperature‐dependent change to reflect food quality status and temperature history. In this paper, a new enzymatic TTI based on enzyme reaction, diffusion, and enzyme demobilization technology is developed. It is considered that the enzyme reaction–diffusion TTI has good stability and reliability at dynamic storage conditions and could be used to monitor the shelf life of perishable food during the cold chain transportation.